Overcrowding an encumbrance for an emergency health-care system: A perspective of Health-care providers from tertiary care center in Northern India - Raman Sharma; Ajay Prakash; Rajeev Chauhan; Deba Prasad Dhibar (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Emergency department (ED) overcrowding is one of the leading problems of health-care organizations, discerned by ED medical staff, but it has never been measured objectively. OBJECTIVE: A 2 months prospective cross-sectional study was conducted to compare ED overcrowding measurement tools with the perceptions of ED emergency physician and ED assistant nursing superintendent (EDEP/EDANS). RESULTS: The results have shown that perceptions of ED overcrowding as noted by EDEP and EDANS, taken on a Likert scale, were 83.34% and 86.67%, respectively. Kappa values show a significant agreement between EDEP and EDANS subjective perceptions with objective values of the National Emergency Department Overcrowding Study (NEDOCS), Real-time Emergency Analysis of Demand Indicators (READI), and Emergency Department Work Index (EDWIN) scales. Furthermore, all three scales have statistically significant correlation; NEDOCS and READI had highest level of correlation coefficient (r = 0.662, P < 0.01) whereas READI and EDWIN shows least correlation coefficient value (r = 0.155, P < 0.01). CONCLUSION: Therefore, these scales may serve to quantify the subjective impressions of ED overcrowding. Evidence is clear of overcrowding harms, measures are needed to provide urgent medical care and future work up is need of the hour to systematically evaluate interventions and guide evidence-based policies.